Психолінгвістичні аспекти асоціативного навчання іноземних мов - Гусак, Людмила; Husak, Ludmyla (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Представлено генезис поняття «асоціація». Повноцінно окреслено суб’єктивно-ідеалістичний і об’єктивно-ідеалістичний напрями асоціативної психології. Особливу увагу звернуто на англійську та американську наукові школи з проблем вивчення асоціативних явищ діяльності психіки. Щодо лінгвістичних трактувань асоціацій у межах психолінгвістики виокремлюють чотири етапи розвитку асоціативних досліджень. Пропонується виділити п’ятий етап дослідження асоціацій, який пов’язаний із вивченням вербальних і невербальних асоціацій та їх використанням у навчанні іноземних мов. Визначено, що метод асоціативних символів є основною технологічною складовою асоціативного навчання іноземних мов учнів початкової школи. Асоціативний експеримент дозволяє дослідити семантичну структуру слова, виявити семантичну схожість між словами в умовах різних культур, розробити методику навчання іншої мови. Окреслено специфіку асоціативної психології. Значну увагу відведено асоціативному експерименту. Обґрунтовано специфіку асоціативної лексикографії.This article deals with the analysis of the psycholinguistic investigations of associations, which is closely connected with the problems of teaching foreign languages to younger pupils. Early learning of the foreign languages causes active searching of the ways of younger pupils’ additional opportunities by employing both hemispheres of head brain. One of the ways of solving this problem is associative teaching the foreign languages that is closely connected with both spheres of younger pupils’ activity: emotional (affective) and intellectual (cognitive). Genesis of the notion “association” is presented in the given article. A special attention is paid to the English and American scientific schools dealing with investigation of the associative phenomena. Concerning the linguistic interpretation of association the author of the article proposes to determine the fifth stage in learning associations, which is closely connected with investigation of verbal and nonverbal associations and their usage in the process of teaching foreign languages. It was stated that associations can be a special model of keeping knowledge in our memory. Cognitivists suppose that there are special nets in our consciousness for keeping information. On the basis of the ideas of associative experiment the method of associative symbols was suggested for teaching English to primary school pupils.
Psycholinguistic Aspects of Associative Teaching of the Foreign Languages
Keywords: асоціація; психолінгвістичні дослідження; вербальні та невербальні асоціації; асоціативне навчання іноземних мов; association; psychological investigations; verbal and nonverbal associations; associative teaching of foreign languages